Modified FOLFIRINOX Versus CISGEM Chemotherapy for Patients With Advanced Biliary Tract Cancer (PRODIGE 38 AMEBICA): A Randomized Phase II Study. Issue 3 (20th January 2022) - Phelip, Jean marc; Desrame, Jérôme; Edeline, Julien; Barbier, Emilie; Terrebonne, Eric; Michel, Pierre; Perrier, Hervé; Dahan, Laetitia; Bourgeois, Vincent; Akouz, Faiza Khemissa; Soularue, Emilie; Ly, Valérie Lebrun; et al.
Abstract : PURPOSE: Whether triplet chemotherapy is superior to doublet chemotherapy in advanced biliary tract cancer (BTC) is unknown. METHODS: In this open-label, randomized phase II-III study, patients with locally advanced or metastatic BTC and an Eastern Cooperative Oncology Group performance status of 0 or 1 were randomly assigned (1:1) to receive oxaliplatin, irinotecan, and infusional fluorouracil (mFOLFIRINOX), or cisplatin and gemcitabine (CISGEM) for a maximum of 6 months. We report the results of the phase II part, where the primary end point was the 6-month progression-free survival (PFS) rate among the patients who received at least one dose of treatment (modified intention-to-treat population) according to Response Evaluation Criteria in Solid Tumors version 1.1 (statistical assumptions: 6-month PFS rate ≥ 59%, 73% expected). RESULTS: A total of 191 patients (modified intention-to-treat population, 185: mFOLFIRINOX, 92; CISGEM, 93) were randomly assigned in 43 French centers. After a median follow-up of 21 months, the 6-month PFS rate was 44.6% (90% CI, 35.7 to 53.7) in the mFOLFIRINOX arm and 47.3% (90% CI, 38.4 to 56.3) in the CISGEM arm. Median PFS was 6.2 months (95% CI, 5.5 to 7.8) in the mFOLFIRINOX arm and 7.4 months (95% CI, 5.6 to 8.7) in the CISGEM arm. Median overall survival was 11.7 months (95% CI, 9.5 to 14.2) in the mFOLFIRINOX arm and 13.8 months (95% CI, 10.9 to 16.1) in the CISGEM arm. Adverse events ≥ grade 3 occurred in 72.8% of patients in the mFOLFIRINOX arm and 72.0% of patients in the CISGEM arm (toxic deaths: mFOLFIRINOX arm, two; CISGEM arm, one). CONCLUSION: mFOLFIRINOX triplet chemotherapy did not meet the primary study end point. CISGEM doublet chemotherapy remains the first-line standard in advanced BTC.